Aspirin and Primary Prevention in Patients with Diabetes—A Critical Evaluation of Available Randomized Trials and Meta-Analyses - Schrör, Karsten; Kristensen, Steen D.; Storey, Robert F.; Verheugt, Freek W. A. (Thrombosis and Haemostasis, 2019)
Primary prevention of cardiovascular events with aspirin in patients with elevated cardiovascular risk, including diabetics, is currently under intense discussion. Data from meta-analyses suggests that the efficacy of aspirin in these patients is low, whereas there is a significantly increased bleeding tendency. However, meta-analyses are based on trials that differ in many important aspects, including study selection. Fresh insights were expected from the ASCEND trial, by far the largest primary, randomized, placebo-controlled prevention trial in diabetics without known cardiovascular disease. There was a small but significant reduction in serious cardiovascular events by aspirin (8.6% vs. 9.6%) but also a significant increase in major bleeding: 4.1% versus 3.2%. Unfortunately, this trial did not meet the desired annual rate of elevated vascular risk of ≥ 2%. It was only 1.2 to 1.3%, and thus in the range of other primary prevention trials in low-risk patients. Apart from potential compliance problems, possible explanations for the small cardioprotective effect of antiplatelet treatment include a healthy lifestyle as well as improved vascular protection by comedication with vasoactive and anti-inflammatory drugs, such as statins or antihypertensive agents, as well as proton-pump inhibitors that might modify bleeding, specifically in the upper gastrointestinal tract—the most frequently affected site. Also, the introduction of new antidiabetic drugs with more favorable cardiovascular effects may in part explain the low event rate. ASCEND, similar to ARRIVE, did not study patients at elevated (as planned) but only at low vascular risk and, therefore, was largely confirmatory of earlier primary prevention trials.
Keywords: diabetes; aspirin; primary prevention; myocardial infarction; bleeding